REFRAMING DEVELOPMENT: GLOBAL PEASANT MOVEMENTS AND THE NEW AGRARIAN QUESTION - McMichael, Philip (REVISTA NERA, 2012)
This paper criticizes the conventional conception of the agrarian question and argues that the way the “agrarian question” is traditionally understood should be revised. The role played by the agrarian movement, especially transnational agrarian movements such as the Vía Campesina, is underscored.